Financing Agric-Business for the Visually Impaired in Nigeria: Issues for Consideration - Pamwal, Ephraim Fomyol (NIU Journal of Social Sciences, 2018)
Issue of finance has always been controversial. This is particular so especially when it comes to the provision of services for special needs individuals in Nigeria. This paper attempts to examine the feasibility of financing agri-business for the visually impaired in Nigeria. This is against be background that concept of financing the visually impaired in agri-business. It examines the benefits and problems of financing such venture for the visually impaired in Nigeria. The paper concludes that through agricultural credit facilities, the visually impaired can benefits from agri-business thereby contributing effectively to sustainable national development.